A molecular phylogenetic assessment of Oxalis L. section Angustatae subsection Lineares using trnL-trnF sequence data - Oberlander, Kenneth (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2003.